Role of Aldo–Keto Reductase Enzymes in Mediating the Timing of Parturition - Byrns, Michael C. (Frontiers in Pharmacology, 2012)
A better understanding of the mechanisms underlying parturition would provide an important step toward improving therapies for the prevention of preterm labor. Aldo–keto reductases (AKR) from the 1D, 1C, and 1B subfamilies likely contribute to determining the timing of parturition through metabolism of progesterone and prostaglandins. Placental AKR1D1 (human 5β reductase) likely contributes to the maintenance of pregnancy through the formation of 5β-dihydroprogesterone (DHP). AKR1C1, AKR1C2, and AKR1C3 catalyze the 20-ketosteroid and 3-ketosteroid reduction of progestins. They could therefore eliminate tocolytic progestins at term. Activation of the F prostanoid receptor by its ligands also plays a critical role in initiation of labor. AKR1C3 and AKR1B1 have prostaglandin (PG) F synthase activities that likely contribute to the initiation of labor. AKR1C3 converts PGH2 to PGF2α and PGD2 to 9α,11β-PGF2. AKR1B1 also reduces PGH2 to PGF2α, but does not form 9α,11β-PGF2. Consistent with the potential role for AKR1C3 in the initiation of parturition, indomethacin, which is a potent and isoform selective inhibitor of AKR1C3, has long been used for tocolysis.